(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda, the science of life, is one of the oldest medical sciences in the world. One among the Great Trio of Ayurveda is Charaka Samhitha by Agnivesha. It is constituted of 120 chapters spread across 8 Sthaanas (sections). The review of references of Madhura across Charaka Samhitha was started by thorough screening using E–Samhitha where Madhura or its synonyms were searched for. The references obtained were tabulated with brief context, application and usage. The literature search of Charaka Samhitha proffered 104 references pertaining to clinical utility of Madhura Rasa were Madhura /its synonyms were directly mentioned. From the 104 references of Madhura Rasa, 14 contexts pointed it out as Nidana – causative factor, 31 contexts as Lakshana – Signs/symptoms/properties and 59 contexts highlighted it as a Chikitsa – treatment/essential regimen. Of these 104 references, 93 were for internal usage and 11 for external utility. Further work towards use of appropriate drugs from Madhura Skandha is essential for beneficial and effective use of Madhura Rasa in clinical practice.